D' Tasty / Muhammad Asyraf Akmal Azmi ... [et al.] - Azmi, Muhammad Asyraf Akmal; Jamil, Muhammad Asyraaf; Muhammad Fauzi, Siti Nawwarah; Kamarul Zaman, Noryamen Aliah; Aziz, Liyana (2016)
D'tasty is the business based on the partnership that made up of five members. The five members consist of General Manager, Administration Manager, Marketing Manager, Financial Manager and Operational Manager. After doing research on the business opportunity available in Taman Universiti, Skudai, Johor, we have decided to specify our business in selling our product. D'tasty is basically a business that based on produce and selling fast foods of salted egg potato chips and salted egg chicken. We create the new type of product that is innovative to sell. D'tasty was registered on 1 st November 2016 and our vision is to be one of the best fast food that produce healthy and halal products in Malaysia and other countries. This vision will be succeeding with the full cooperation and efforts among the partners in managing this business. Based on the objective, we venturing into food industry because it has the potential of being a profitable business if it is done in luxury and innovative way with the large scale. This is because the majority of this resident in this area is a Chinese. The contribution of our price is RM22,000 from general Manager and RM19, 500 from each of the partnership member a capital this business. We hope that our business will became more developed a in the future because o the demand for this food is high and no companies that produce innovative product that meets the wants of consumers and buyers. This will give us more advantages to globalize our product to be more profitable and stable for the long time.